2007
DOI: 10.1007/s00127-007-0240-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of health service use among Iraqi asylum seekers in the Netherlands

Abstract: j Abstract Background A long asylum procedure is associated with higher prevalence rates of psychiatric disorders, lower quality of life, higher disability and more physical health problems. Additional knowledge about health seeking behavior is necessary to guide governments and health professionals in their policies. Objective To measure service use among one of the biggest asylum seekers population in the Netherlands and to assess its relationships with predisposing and need variables (including post-migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 23 publications
(28 reference statements)
6
80
1
5
Order By: Relevance
“…45 Compared with those who had arrived within the previous 6 months, asylum seekers with a longer length of stay had a higher level of disability, greater physical complaints, perceived lower physical health status and lower quality of life. 36,37 Longer length of stay was also associated with a lower live birth and abortion rate among asylum seekers. 33 A greater number of pre-migration traumatic events resulted in higher medical referral rates, 26 and was associated with chronic conditions and poor general health status.…”
Section: Sociodemographic Determinants Of Physical Healthmentioning
confidence: 97%
See 2 more Smart Citations
“…45 Compared with those who had arrived within the previous 6 months, asylum seekers with a longer length of stay had a higher level of disability, greater physical complaints, perceived lower physical health status and lower quality of life. 36,37 Longer length of stay was also associated with a lower live birth and abortion rate among asylum seekers. 33 A greater number of pre-migration traumatic events resulted in higher medical referral rates, 26 and was associated with chronic conditions and poor general health status.…”
Section: Sociodemographic Determinants Of Physical Healthmentioning
confidence: 97%
“…[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Compared with other population groups using the same outcome measures, perception of poor general health status was much worse among asylum seekers (around 60% 32,42 ) than comparative refugee samples (around 42% 32,42 ), immigrants (39% 32 ) or a general, non-immigrant population (18% 32 ).…”
Section: Physical Health Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Within Europe the large majority (80–90%) of refugees with symptoms of PTSD or other psychological problems (Laban, Gernaat, Komproe, & De Jong, 2007; Lamkaddem et al, 2014) do not visit specialized mental health care services. Other barriers include language problems (Bischoff et al, 2003), physical distance to mental health care services since refugees are often located in rural areas, and an overall lack of Arabic speaking psychologists or psychotherapists in European countries hosting Syrian refugees.…”
Section: Barriers To Mental Health Care For Refugeesmentioning
confidence: 99%
“…In the course of the 7 year follow-up period, the proportion increased to 54%, but remained relatively low (www.gezondheidsraad.nl). Another study (Laban, Gernaat, Komproe, & De Jong, 2007) in the Netherlands found that only 9% of asylum seekers with mental disorders had visited a mental health institution.…”
Section: Prevalence Of Mental Disorders Among Refugeesmentioning
confidence: 99%